REVITALISASI PERATURAN PERUNDANGAN-UNDANGAN SEBAGAI UPAYA STRATEGIS PENANGANAN DAMPAK PERUBAHAN IKLIM DI INDONESIA - Hilman, Dadang (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
Current impact of climate change, especially extreme events(such as: heat wave in northem hemisphere or extremely heavyrainfall in Java) and climate related-disasters (like: flood,drought, landslides, forest fires, etc) is increasingly felt bypeople, has led to climate change is now not just an issueanymore, it has become a real problem that to be tackled notonly through international level through multilateral approach(convention), but also through national/local level.This complex problem has challenge all of us, of course basedon its role and capacity. Considering its nature that iscomplicated and cross-sectoral as well as affecting to all people,to cope with this problem we have to apply multi-layerapproaches. It needs to involve active role of all layers ofgovernment/ administration from central, including the Houseof Representatives), until the lowest level (village/desa/kelurahan), not only environment related institutions but alsoall components of the nation.From the view of top-down approach, one of strategic and long/medium-term steps is revitalization (including reviewing andgradual revision) of all relevant acts and regulations until itcreated a new products of law that are not only implementablebut also contribute significantly to problem solving as well asanticipative measures that could help reduce possilbe climaterisks in the near future. This could be achieved only by creatinga ‘climate proof or climate smart’ law system.